Analysis of Students’ Critical Thinking Improvement in Teaching Inquiry with Cognitive Conflict Strategies - Verawati, Ni Nyoman Sri Putu; Hikmawati, Hikmawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aimed to analyze the improvement of students’ critical thinking skills in teaching inquiry with cognitive conflict strategies. Quasi experiments were conducted in this study. The research sample was twenty students as physics teacher candidates at a private university in West Nusa Tenggara - Indonesia. The critical thinking skills test instrument in the form of essay questions is used to measure students’ critical thinking skills. The analysis of increasing of critical thinking skills was analyzed descriptively with the n-gain equation, and the difference in critical thinking skills between the pretest and posttest using a pair t-test which was preceded by homogeneity and normality tests. The results of the n-gain analysis showed that the increase in students’ critical thinking scores was in the moderate category. Qualitatively, the increase in scores from pretest to posttest in a row is from not critically to enough critically. The results of this study imply that inquiry teaching with cognitive conflict strategies has the potential to be implemented in classroom teaching for the purpose of improving students’ critical thinking skills.